Fingerprint Matching Algorithms and BOVW: A Survey - Suresh, Y; Srinivasu, S.V. N (International Journal of Computer Sciences and Engineering, 2018)
In recent years, the use of biometrics has increased exponentially in the areas where security is a playing vital role. The factors that increasing the use of biometric in many applications include: the cost of the devices which are used for capturing and storing the images are greatly reducing, the ease-of-use of available devices, availability of fast hardware devices which are used for computing, the increasing use of networking and internet technology, different algorithms are available for storing the images in compressed format, etc. The role of biometric application is to authenticate the person by their voice, face or fingerprint. In biometric system, finger print is an extensively accepted one because of its advantage like no two person’s finger prints are same in the universe. In this paper we are presenting the detailed survey on fingerprint matching algorithms.